Inhibitory Activity Test of Sea Grape (Caulerpa racemosa) Against Salmonella typhi Bacteria - Indri J. Kereh; Yessie K. Lengkey; Sonny D. Untu; Margaretha S. Ginting; Ferdy A. Karauwan; Selvana S. Tulandi; Adolfina Sumagando (FMIPA UKIT, 2025)
Salmonella typhi is the primary bacterial cause of typhoid fever, which remains a serious health concern in developing countries, including Indonesia. This study aims to evaluate the inhibitory activity of sea grape (Caulerpa racemosa) extract against Salmonella typhi. The extract was obtained through maceration and tested using the agar diffusion method with paper discs at various concentrations (100, 200, 300, and 400 µg/disc). The results showed that C. racemosa extract inhibited the growth of S. typhi with average inhibition zone diameters of 25 mm (100 µg), 27.3 mm (200 µg), 28.8 mm (300 µg), and 29.5 mm (400 µg). The negative control (distilled water) showed no antibacterial activity. Based on classification, all concentrations exhibited very strong antibacterial activity. A higher extract concentration corresponded to greater inhibitory effect. These findings suggest that C. racemosa has potential as a natural antibacterial agent against S. typhi and may be further developed for alternative typhoid treatment.